Examining the assessment literacy required for interpreting score reports: A focus on educators of K–12 English learners. (January 2020) - Kim, Ahyoung Alicia; Chapman, Mark; Kondo, Akira; Wilmes, Carsten
This study investigated the assessment literacy required for K–12 educators to interpret score reports from a K–12 English language proficiency assessment. The assessment in concern is ACCESS for ELLs, which is an annual summative assessment that is delivered to nearly 2 million English learners (ELs) across 39 US states and territories. This study was conducted in two phases. In Phase 1, an online teacher survey, consisting of 15 items, was completed by 1437 participants; data were analyzed using descriptive statistics. In Phase 2, 18 educators were interviewed to obtain in-depth understanding of educators' interpretation of the score reports. Interview data were qualitatively analyzed in terms of (1) the essential assessment literacy required for interpreting the score reports, (2) resources referred to by educators for score report interpretation, and (3) educators' suggestions to enhance the score report and its interpretation. The findings of the study reveal the relevance of K–12 EL educators' assessment literacy for score report interpretation. For example, educators referred to proficiency level scores the most, but experienced difficulty in understanding technical terms, such as "scale scores" or "confidence band." The results provide implications for enhancing the quality of score reports and the development of resources to support educators' assessment literacy.